Influence Of Float Volume On Helicopter Flotation Stability - Tödter, S.; Peters, A.; Neugebauer, J.; Harms, S.; Moctar, O. el (My University, 2025)
The dynamic flotation stability of helicopters during ditching is a major safety concern for offshore operations. Studies have shown that most ditching fatalities are caused by capsizing and subsequent drowning of passengers and crew. Model-scale experiments were performed to analyse the roll, pitch and heave motions of a light multipurpose helicopter after ditching in a seaway with a significant wave height of 6 m. The capsize events and their occurrence probabilities for a helicopter equipped with cylindrical floats of different sizes were analysed and compared for three different float volumes. It was found that increasing the float size only had a minor effect on flotation stability.